Diferença da permeabilidade in vitro do stent de nitinol revestido com a membrana regeneradora porosa comparado com o stent de nitinol sem revestimento - Reis, Rosane Pereira dos (2020)
Context: Vascular permeability is the ability of the vessel to let liquid out of the vessel. Currently, one of the great needs is to find an endoprosthesis that maintains the laminar flow, without occluding the visceral vessels, for endovascular treatment of complex aneurysms. However, stents are braided metal structures, with meshshaped opening at the bottom and top, which have good visibility and flexibility, introduced into the vascular lumen. In the current reality, stents have become an interesting alternative, less invasive and increasingly accessible to the population affected by vascular problems, whose function is to maintain the patency of the vessel and prevent restenosis resulting from the development of myointimal hyperplasia. Objective: To determine the difference in in vitro permeability of the nitinol stent coated with the porous regenerating membrane compared to the nitinol stent without coating. Hypothesis: The difference in in vitro permeability of the nitinol stent coated with the porous polyester membrane compared to the uncovered nitinol stent is greater than 30% and less than 50%. Study type: In vitro and comparative experimental study. Sample: The sample was probabilistic, for convenience, the sample size was arbitrated in 12 stents, being 06 (six) for each group studied. Variable: The difference in in vitro permeability of the nitinol stent coated with a porous regenerating membrane compared to the uncovered nitinol stent. Results and Discussion: The results showed that the uncoated nitinol stent had an average in vitro permeability index of 790.7 ml, while the nitinol stent coated with porous regenerating membrane had an average permeability index of 268.4 ml, which demonstrates the importance of the association of this membrane with the stent, as it reduces the permeability and allows it to be used in complex aneurysms, without having to use three layers of metal. Conclusion: This new stent model coated with the porous regenerating membrane turned out to be more efficient than the stent without coating, proving a permeability of 49.31%.